Microglia P2Y13 Receptors Prevent Astrocyte Proliferation Mediated by P2Y1 Receptors - Clara Quintas; Clara Quintas; Nuno Vale; Nuno Vale; Jorge Gonçalves; Jorge Gonçalves; Glória Queiroz; Glória Queiroz (Frontiers Media S.A., 2018)
Cerebral inflammation is a common feature of several neurodegenerative diseases that requires a fine interplay between astrocytes and microglia to acquire appropriate phenotypes for an efficient response to neuronal damage. During brain inflammation, ATP is massively released into the extracellular medium and converted into ADP. Both nucleotides acting on P2 receptors, modulate astrogliosis through mechanisms involving microglia-astrocytes communication. In previous studies, primary cultures of astrocytes and co-cultures of astrocytes and microglia were used to investigate the influence of microglia on astroglial proliferation induced by ADPβS, a stable ADP analog. In astrocyte cultures, ADPβS increased cell proliferation through activation of P2Y1 and P2Y12 receptors, an effect abolished in co-cultures (of astrocytes with ∼12.5% microglia). The possibility that the loss of the ADPβS-mediated effect could have been caused by a microglia-induced degradation of ADPβS or by a preferential microglial localization of P2Y1 or P2Y12 receptors was excluded. Since ADPβS also activates P2Y13 receptors, the contribution of microglial P2Y13 receptors to prevent the proliferative effect of ADPβS in co-cultures was investigated. The results obtained indicate that P2Y13 receptors are low expressed in astrocytes and mainly expressed in microglia. Furthermore, in co-cultures, ADPβS induced astroglial proliferation in the presence of the selective P2Y13 antagonist MRS 2211 (3 μM) and of the selective P2Y12 antagonist AR-C66096 (0.1 μM), suggesting that activation of microglial P2Y12 and P2Y13 receptors may induce the release of messengers that inhibit astroglial proliferation mediated by P2Y1,12 receptors. In this microglia-astrocyte paracrine communication, P2Y12 receptors exert opposite effects in astroglial proliferation as a result of its cellular localization: cooperating in astrocytes with P2Y1 receptors to directly stimulate proliferation and in microglia with P2Y13 receptors to prevent proliferation. IL-1β also attenuated the proliferative effect of ADPβS in astrocyte cultures. However, in co-cultures, the anti-IL-1β antibody was unable to recover the ADPβS-proliferative effect, an effect that was achieved by the anti-IL-1α and anti-TNF-α antibodies. It is concluded that microglia control the P2Y1,12 receptor-mediated astroglial proliferation through a P2Y12,13 receptor-mediated mechanism alternative to the IL-1β suppressive pathway that may involve the contribution of the cytokines IL-1α and TNF-α.